Vitamins Affecting the Function of The Nervous System - Jalolova Ozoda Kosimjanovna; Kodirov Sherzodbek (Zien Journals, 2022)
Is a system that the nervous system plays a crucial role in the evolution of the animal organism and in the formation of complex relationships between organisms and the external environment.
Keywords: Nervous system; vitamins